(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
Adolescent obesity combined with environmental iodine deficiency creates multifactorial risks for male reproductive maturation. This cross-sectional study examined 184 boys aged 14 to 17 years from iodine-deficient areas, comparing testicular volume, spermatogenic markers, and hypothalamic-pituitary-gonadal axis function between normal-weight and overweight cohorts. Overweight adolescents demonstrated significantly reduced testicular volumes, lower serum testosterone concentrations, impaired sperm parameters, and disrupted thyroid homeostasis compared to controls, suggesting synergistic endocrine disruption warranting targeted clinical intervention.